IMPACT OF ACCREDITATION ON THE QUALITY OF MADRASAH ALIYAH EDUCATION (STUDY AT MAN I EAST LAMPUNG, MA MUHAMMADIYAH PURBOLINGGO AND MA MAARIF NU 8 TAMAN CARI IN EAST LAMPUNG DISTRICT - SOLIKHATI, Zuni INSI (Universitas Pendidikan Indonesia, 2020)
Based on the analysis of research data it can be concluded that the impact of accreditation in MAN 1 Lampung Timur, namely: National exams and madrasah final exams with national standard, the average score reaches 9.6 and passes 100%. Community trust is increasing. the impact of accreditation in MA Muhammadiyah Purbolinggo. Accreditation is one of the ways carried out by the stakeholders in this matter the government to evaluate and control the education that has been carried out and all components and stakeholders have produced encouraging results including one of them getting an accreditation rating rank B. Impact of Accreditation MA Ma'arif NU 8 Taman Cari Public trust in the institution is increasing. Student achievements of MA Ma'arif NU 8 Taman Search both academically and non-academically, students' faith and devotion to Allah SWT is increasing. Madrasah accreditation scores reach B, which is Good.